THE EFFECTS OF ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE IN SUMEDANG SELATAN DISTRICT OFFICE SUMEDANG REGENCY - Febianti, Fepi; Nurwan, Teddy Marliadi (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2021)
The core of the problem in this study is to determine the effects of organizational culture on employee performance in Sumedang Selatan District Office, Sumedang Regency. This study aims to determine the implementation, correlation, and effects of organizational culture on employee performance in Sumedang Selatan District Office, Sumedang Regency. This study used a survey method. Data collection techniques used were observation, interviews, questionnaires, and data processing related to the problems studied namely organizational culture and employee performance. The analysis technique used is a simple regression analysis, correlation test, coefficient of determination, and hypothesis testing. The research sample used as many as 46 people, namely all civil servants in Sumedang Selatan District Office. The results of quantitative calculations were obtained based on the value of the Pearson correlation (r). It is known that the r value for the effects of organizational culture (X) on employee performance (Y) is 0.713 r table 0.290. So it can be concluded that there is a correlation between the organizational culture (X) to employee performance (Y).